Women's Decision-Making about PrEP for HIV Prevention in Drug Treatment Contexts. (9th January 2020) - Qin, Yilu; Price, Carolina; Rutledge, Ronnye; Puglisi, Lisa; Madden, Lynn M.; Meyer, Jaimie P.
Despite pre-exposure prophylaxis's (PrEP) efficacy for HIV prevention, uptake has been low among women with substance use disorders (SUDs) and attributed to women's lack of awareness. In semistructured interviews with 20 women with SUD and 15 key stakeholders at drug treatment centers, we assessed PrEP awareness and health-related decision-making. Women often misestimated their own HIV risk and were not aware of PrEP as a personally relevant option. Although women possessed key decision-making skills, behavior was ultimately shaped by their level of motivation to engage in HIV prevention. Motivation was challenged by competing priorities, minimization of perceived risk, and anticipated stigma. Providers were familiar but lacked experience with PrEP and were concerned about women's abilities to action plan in early recovery. HIV prevention for women with SUD should focus on immediately intervenable targets such as making PrEP meaningful to women and pursuing long-term systemic changes in policy and culture. Efforts can be facilitated by partnering with drug treatment centers to reach women and implement PrEP interventions.